2018
DOI: 10.1111/apa.14555
|View full text |Cite
|
Sign up to set email alerts
|

Facilitated tucking during early neonatologist‐performed echocardiography in very preterm neonates

Abstract: Echocardiography performed soon after birth in very premature neonates may generate mild discomfort. FT during echocardiography is associated with lower pulmonary artery pressures and improves infant's comfort during this examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…54 Another advantage is that it is effective for extremely or very premature infants without requiring any other abilities, such as mature sucking ability. 55 Moreover, it can be used when newborns are unable to be transferred from the incubator or bed. 26 SSC, also known as KC, refers to the way the mother holds a diaper-clad infant upright on her breast at approximately 60°, providing maximum skin-to-skin contact between the baby and mother.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…54 Another advantage is that it is effective for extremely or very premature infants without requiring any other abilities, such as mature sucking ability. 55 Moreover, it can be used when newborns are unable to be transferred from the incubator or bed. 26 SSC, also known as KC, refers to the way the mother holds a diaper-clad infant upright on her breast at approximately 60°, providing maximum skin-to-skin contact between the baby and mother.…”
Section: Discussionmentioning
confidence: 99%
“… 54 Another advantage is that it is effective for extremely or very premature infants without requiring any other abilities, such as mature sucking ability. 55 Moreover, it can be used when newborns are unable to be transferred from the incubator or bed. 26 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another source of ventilation perfusion mismatch, clearly demonstrated in our patient, was the alterations in vascular tone, leading to PH, an increase in pulmonary vascular resistance, and ductal right-left shunting. Based on our experience, a peak tricuspid regurgitant jet velocity reaching 3 m/s was clearly high for this patient, corresponding to approximately double the velocity we usually record in premature infants [ 46 ]. Using a relevant M-mode echocardiography index to assess pulmonary haemodynamics, a study in stable low birthweight neonates suggested increased pulmonary vascular resistance during the infusion of 0.6 g/kg of a pure soybean oil emulsion over 2 h [ 47 ].…”
Section: Discussionmentioning
confidence: 80%
“…The infant is held in a flexed foetal‐type position with its limbs close to the midline of the torso. In this issue of Acta Paediatrica, Gautheyrou et al report the findings of their randomised controlled trial of the use of facilitated tucking in very preterm neonates below 30 weeks of gestation during early NPE. The primary outcome was the effect that facilitated tucking had on echocardiographic indexes of pulmonary haemodynamics.…”
mentioning
confidence: 99%